Analysis of factors affecting fear and mental health awareness of coronavirus disease infection - Nursalam, Nursalam; Hapsari, Elsi Dwi; Setiawan, Setiawan; Agustini, Ni Luh Putu Inca; Priyantini, Diah; Khatijah Lim, Abdullah * (Faculty of Nursing Universitas Airlangga, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) is a global health challenge that persists in causing both health emergencies and mental health crises around the world. This study aimed to analyze the factors contributing to COVID-19 infection and their impact on mental health crises on Java Island.